AN ASSESMENT OF NUTRIENT CONTENT OF UNDERUTILIZED GRASS SPECIES OF SOUTH INDIA - R. HARI BABU; N. SAVITHRAMMA (International Journal of Pharma and Bio Sciences, 2013)
In the past and now most of the developments in conventional agriculture have concentrate on major grasses with little attention to the minor, underutilized grasses and as yet undeveloped grasses of livestock. Many underutilized grass species are being lost each day and more of which have unknown potential will be lost. The present study is undertaken to carry out the nutrient content of twenty grass species of family Poaceae, commonly found in waste lands of South India to screen some nutritive values. The Moisture content of the grass species varied between 42% to 71%, Protein content 1.66% to 5.43%, Sugar 1 % to 3.54%, Starch from 7% to 17.74% and Cellulose ranged from 1.79% to 7.60% of dry weight. Among the twenty grass species Eragrostis amabilis showed high nutritive value, followed by Cynodon dactylon, Pycreus flavidus, Digitaria sanguinalis and Brachiaria racemosa. Hence these grass species of high nutritive value can be choosen for feeding the live stock.